Teks Agama dalam “Midnight Children” oleh Salman Rushdie: Sebuah Kajian Intelektual - Mayasari, Tri Rahayu (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This study explores religious texts in Salman Rushdie's novel Midnight's Children, with a focus on intertextual analysis. The theory employed to analyze the novel is Wolfgang Iser's theory of repertoire studies. The research method utilized is qualitative descriptive. The findings of the study reveal the presence of hypograms from various previous works or texts within Midnight's Children. Specifically, there are four religious discourses serving as hypograms: the Holy Quran, Al-Hadith Bukhari, the book Alfu Layla wa Layla, and the story of the descent of Adam and Eve. Additionally, the research identifies a significant influence of these prior texts, particularly religious scriptures, on Midnight's Children. The process of transforming the hypograms into the forms observed in the novel undergoes modification and adjustment.